Technographismes en ligne. Énonciation matérielle visuelle et iconisation du texte - Marie-Anne Paveau (Corela)
In the context of visual studies, Mitchell (1994) showed that the image increasingly organizes our semiotic perception, by re-correlating the production of meaning in an iconic perspective. The hypothesis of an « image-becoming » (Nachtergael 2017) of text, discourse and interaction is therefore not new but seems to be confirmed by digital communication, where image plays an important role, reorganizing meaningful content and sometimes taking precedence over verbal expression within technographism, defined as a native digital multimedia production articulating image, text and possibly sound (Paveau 2017). In this article, I propose to implement this hypothesis using the example of printed or on-screen text photography, which is increasingly integrated into native digital speech, especially on social networks such as Twitter or Facebook. I will show that it is an iconization of the text, testifying to a digital conversion of scripturality and raising the question of a contemporary piloting of meaning through the image.